A Legacy of Loss: No Return Address: Partition and Stories of Displacement - Marino, Elisabetta (Testo e Senso, 2023)
76 years have elapsed since the dramatic Partition of the Indian Subcontinent: yet, its specter continues to loom large over the three countries that were established following the end of the Raj and the liberation war that led to the formation of Bangladesh, in 1971. In an effort to shed light on the still underexplored partition of Bengal, Manjira Majumdar has compiled and edited a collection of ten short stories and a longer fictional piece meaningfully entitled No Return Address: Partition and Stories of Displacement (2022). This essay sets out to investigate the feelings of uprootedness and loss experienced by the protagonists, longing for a place to belong.